Exoscope-assisted spine surgery: Current applications and future directions–A short review - Tomas Ferreira; Sakshi Roy; Joecelyn Kirani Tan; Wireko Andrew Awuah; Vallabh Shet; Favour Tope Adebusoye; Adrenito Nicolas; Toufik Abdul-Rahman (World Neurosurgery: X)
Spine surgery is a critical field that seeks to alleviate pain and restore function in patients with various spinal pathologies. Over the years, spine surgery has seen advancements such as minimally invasive techniques with operative microscopes and robotic surgeries. These techniques, however, demand better visualisation during the procedure. Recently, exoscope-assisted spine surgery has emerged as a promising technological advancement that may revolutionise the field due to its ability to facilitate precise and advanced visualisation techniques that ensure successful outcomes in spine surgeries. The application of exoscopes have improved spine surgeries such as spinal fusion procedures, decompression surgeries, instrumentation surgeries, minimally invasive and complex surgeries. These improvements include enhanced visualisation, improved ergonomics, improved surgical precision, reduced operation times and postoperative infection rates. The integration of robotics in exoscope-assisted spine surgery enables autofocus function, ensuring the integrity of the sterile field, providing superior image quality, resolution and three-dimensional perception. However, challenges such as decrease in depth perception and the lack of long-term follow-up data hinder its widespread adoption. Ethical considerations regarding patient safety, technology dependency, and health inequity add another dimension to these challenges. Despite these challenges, exoscope-assisted spine surgery holds significant potential for transforming clinical practice and improving patient outcomes. This review seeks to provide a concise overview of the benefits and limits of exoscope-assisted spine surgeries, while highlighting its challenges and ethical considerations. Addressing these limitations by conducting large-scale clinical trials and exploring the integration of artificial intelligence (AI) could assist in realising the potential of exoscopes in spine surgery.